Climate change in Ugandan media: A 'Global Warming' of journalism ethics. (1st September 2013) - Semujju, Brian
The idea of climate change has reached a contentious breaking point at an international level where its major causes, existence and intensity are separating informed minds. This article is an examination of the four major schools of thought on climate change and how two newspapers in Uganda are covering those divergent views. The article argues that in the coverage of global warming in particular the hitherto treasured notion of objectivity has been replaced by a form of blind journalism instigated by frames from local and international stakeholders. The study analyses content from two newspapers in Uganda to show that media in Uganda cover the resonating frame, which argues that climate change is a time bomb, with total disregard for other views or their existence. Guided by the framing theory, the article suggests that a detachment of climate change from international meanings and an introduction of the 'scientific spirit' will restore balance by inviting media to explore counter-frames.